Case report: Assessment of linguistic, cognitive, and sensory profile competencies in a child with ASD and epilepsy - Cano-Villagrasa, Alejandro; Porcar-Gozalbo, Nadia; López-Chicheri García, Isabel; López-Zamora, Miguel (Frontiers in Psychology, 2024)
Introduction Autism Spectrum Disorder (ASD) and epilepsy pose significant challenges for early diagnosis during childhood. Current scientific literature does not reflect robust action protocols that allow for a detailed screening of difficulties in this population, especially in areas such as language, cognition, and sensory profile. Additionally, detecting epilepsy before the age of 4 is established as a major current public health challenge in our society. Objective The aim was to evaluate a patient exhibiting symptoms compatible with both ASD and epilepsy, determining the linguistic, cognitive, and sensory profile through a clinical assessment protocol. Furthermore, the objective included establishing a diagnosis of ASD. Method This single-case study (N = 1) presents the evaluation of a 7-year-old patient with suspected ASD, experiencing a decline in linguistic and cognitive competencies following a documented epileptic episode. Evaluation was conducted using instruments such as CELF-5, PROLEC-R, WISC-V, ENFEN, PS-2, ADI-R, and ADOS-2. Results Following assessment of language, cognition, sensory aspects, and behaviors associated with ASD, the diagnosis of ASD was confirmed in the patient, along with impairments in expressive and receptive language, executive functioning, and alterations in the sensory profile. Conclusion Diagnosing ASD and epilepsy, as well as their evaluation, is a complex process requiring interdisciplinary assessment involving a detailed exploration of all functional competencies in individuals with this comorbidity. Future studies should focus on creating and improving existing protocols to develop optimal and effective evaluation strategies for assessing this population during childhood.